KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK SABUN CAIR PENCUCI TANGAN HANDMADE BERBAHAN AMPAS SISA KOPI ESPRESSO - Asri Widyasanti; Arinda Nur Ariva (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
The utilization of cofee residue is still limited. Usually the remaining cofee pulp is used as fertilizer for plant growth nutrition with hydroponic media, insect repellent, air freshener and deodorizing agent. Apparently, coffee grounds pulp can still be used to treat skin. One of the efforts to increase the added value of espresso coffee residue is to be used as handmade hand-washing soap by the CSR Indonesia Kamojang POMU community. The purpose of this study was to determine the physical, chemical, and organoleptic characteristics of hand washing soap made from the residue of espresso coffee grounds. The method used in this study was a laboratory experiment with descriptive analysis. Observations on liquid soap include chemical properties, physical properties, and organoleptic tests. The results of the analysis showed that the formulation of the residual soap of espresso coffee had pH 7.9 and specific gravity 1.034. Organoleptic test results on the level of preference for the resulting liquid soap product hand washing coffee grounds, each with a score for: color = 2.83 (dislike-netral), viscosity = 2.83 (dislike-netral), aroma = 2, 83 (dislike-netral), impression when using / foaming = 3.25 (netral-like), and impression after use (impression rough) = 3.08 (netral-like). The technology process of making handmade hand washing liquid soap with the addition of the remaining espresso coffee residue then continue to be developed so that it can be applied on an industrial scale.Keywords: Characteristics, Handmade soap, Hand Washing, Residue Coffee, Espresso